Biodiversity of the aculeate wasps (Hymenoptera: Aculeata) of the Arabian Peninsula: Vespoidea, Vespidae - Carpenter, James M.; Gadallah, Neveen S. (Zootaxa, 2020)
An updated checklist of the Arabian species of Vespidae is provided here. The list includes 163 identified species in 49 genera and four subfamilies: Eumeninae (41 genera, 130 species), Masarinae (4 genera, 14 species), Polistinae (3 genera, 17 species) and Vespinae (1 genus, 2 species). Distributions, both on the Peninsula and extra-limital, are provided for each species and subspecies; 53 species (33%) are endemic to the Arabian Peninsula, as are 15 subspecies. A new combination is proposed: Knemodynerus sauditus (Giordani Soika, 1989) comb. nov., transferred from Trachyodynerus Giordani Soika, 1989.